2008
DOI: 10.1111/j.1525-1470.2008.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Tacrolimus in the Treatment of Lichen Planus in a Child

Abstract: Lichen planus is a relatively common mucocutaneous disease in adult patients, but it is more rare in children. Topical corticosteroids are the first line of treatment in most pediatric patients with a localized classic form of lichen planus. We report the case of a child with cutaneous lichen planus who did not respond to topical steroids but showed complete resolution once switched to 0.03% tacrolimus ointment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…There are few reports 21–23 on successful use of topical tacrolimus in LP, especially oral LP, and there is a single report 24 on failure of topical tacrolimus in LPP. One reason for the failure of tacrolimus could be that the authors had used it only for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports 21–23 on successful use of topical tacrolimus in LP, especially oral LP, and there is a single report 24 on failure of topical tacrolimus in LPP. One reason for the failure of tacrolimus could be that the authors had used it only for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Topical tacrolimus has been reported as a safe, effective therapy for cutaneous (5,6), oral (7-9) and vulvar lichen planus (LP) (9)(10)(11), even in patients whose lesions have shown recalcitrance to other treatments (7,10). However, topical tacrolimus treatment for NLP has never been reported.…”
Section: Sirmentioning
confidence: 96%
“…Oral agents that can be used for mucosal LP are systemic glucocorticoids, griseofulvin, hydroxychloroquine, azathioprine and mycophenolate mofetil. Intraleisonal triamcinolone may be used [29] Short courses of systemic steroids have been found to be effective in widespread eruptive disease, given at a dose of 1-2 mg/kg/day for one-two weeks and then weaned. [30,31] Nanda et al has observed that UVB phototherapy is safe and effective in children with acute widespread LP.…”
Section: Treatment and Prognosismentioning
confidence: 98%